CORRELATION BETWEEN HOUSE DUST MITE DENSITY WITH HEALTHY HOUSE CRITERIA AND ASTHMA STATUS IN PEDIATRIC PATIENTS - Shobrina Insan Sakina Armunanto; Dian Puspita Dewi; Dodik Pramono; Moh Syarofil Anam (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Abstract Background: Asthma is a chronic respiratory disease most often found in children and has the highest prevalence in developing countries. House dust mites are the second most common trigger of asthma whose habitat is influenced by the criteria for a healthy.Objective: Understanding the correlation between sleep density and asthma status in pediatric patients and criteria for a healthy house.Methods: This study was an analytical observational method with a cross sectional study design that took place from June to October 2020. It involved 25 respondents of children with asthma patients aged 3-11 years. There is a confounding variable, namely the criterion score for a healthy house. Dust samples were collected in the bedroom of the respondent diagnosed with bronchial asthma. The identification process using the floating method was carried out at the Parasitology Laboratory, Faculty of Medicine, Diponegoro University, Semarang Indonesia. Respondent data were analyzed using statistical software programs. Non-parametric test with lambda correlation test.Results: The mean of house dust mite’s density in the respondent's house was 3.68 ± 2.32. House dust mite’s density was associated with the criteria for a healthy house (p <0.05), but house dust mite density was not related to the asthma status of pediatric patients (p> 0.05).Conclusion: There is no correlation between pediatric asthma status and house dust mite density.